Embryo Development and Behavior in Sea Urchin (Tripneustes gratilla) Under Different Light Emitting Diodes Condition - Li, Yi-Yen; Su, Feng-Jie; Hsieh, Yi-Jui; Huang, Tai-Chun; Wang, Yung-Song (Frontiers in Marine Science, 2021)
This study aims to evaluate the effect of light-emitting diodes (LEDs) of different wavelengths on the embryonic development, covering behavior, righting behavior, and phototaxis of collector urchins (Tripneustes gratilla). The collector urchins were divided into three groups according to the type of LED illumination they received: full-spectrum (400-750 nm wavelength), red light (630 nm), or blue light (450 nm). The results of the embryonic development experiment indicated that the blue LED group had the highest proportion of embryos reaching the prism stage at the 24th hour and the highest proportion of embryos entering the 4-arm pluteus stage, but it also had the highest death rate at the 48th hour. The full-spectrum and red LED groups exhibited similar speeds of embryonic development. In the experiment on covering behavior performed on adult urchins, our findings indicated that the blue LED group gripped the most acrylic sheets for cover, exhibiting the most covering behavior, followed by the full-spectrum group and then the red LED group. Moreover, behavior varied with coloration, as collector urchins with a lower level of melanin exhibited more covering behavior than those with a higher melanin level. In addition, the righting behavior experiments demonstrated that the blue LED group spent the longest time righting themselves. It is possible that the relatively strong stimulation from the blue LED illumination led to a higher level of stress in the collector urchins and hence slowed their righting. The phototaxis experiment revealed the most significant negative phototactic response in collector urchins when they were under the blue LED light, followed by the full-spectrum light; the red LED light did not induce any positive or negative phototactic response in the collector urchins. This experimental result verified collector urchins’ high sensitivity to and dislike of the blue LED light. The study results confirmed that the blue LED light environment accelerated the embryonic development of collector urchins; however, the relatively strong stimulation from that light also caused them to engage in covering behavior or move away from the light. These results indicate that short-wavelength irradiation significantly affects the embryonic development and behavior pattern of this species.